The Effect of Human Resource Competency Development on The Productivity of Salted Fish UMKM Centers In Pulau Pasaran Lampung - Titin Rosdyanti; Bunga Aditi; Pratama, Reza Hardian; Eka Gustinasari; Elita Yuni Setiyarini (Yayasan Inovasi Kemajuan Intelektual, 2024)
National economic growth is supported by micro, small, and medium enterprises (MSMEs). To meet community needs, this study analyses the influence of human resource (HR) competency development on the productivity of salted fish MSMEs in Pasaran Island, which is known as a traditional fish processing centre in Bandar Lampung, Indonesia. The research focuses on four key indicators of HR competency: technical skills training, improvement of managerial abilities, mastery of simple technology, and participation in certification or quality improvement programs. A quantitative associative approach was employed, involving 100 respondents selected through purposive sampling. Data were analysed using Partial Least Squares-Structural Equation Modelling (PLS-SEM) with SmartPLS 3.2.9. The results show that all four variables significantly affect MSME productivity, with certification or quality improvement programs having the strongest influence. These findings highlight the importance of structured HR development strategies in enhancing production efficiency, product quality, and business sustainability. This study provides theoretical contributions to HR management science and practical recommendations for MSME actors and policymakers in improving the competitiveness of traditional fish processing industries at both local and national levels. The finding that certification or quality improvement programs have the strongest influence provides new empirical evidence that formal legitimacy (certification) and quality standardisation are integral to HR development. The results also emphasize the importance of participating in technical training, improving managerial abilities, mastering simple technology, and actively participating in certification programs to enhance productivity and product quality.